2013
DOI: 10.1017/s0950268812002713
|View full text |Cite
|
Sign up to set email alerts
|

Update on diversity and distribution of HIV-1 subtypes in Yunnan province

Abstract: The aim of this study was to characterize updated HIV subtypes in Yunnan to determine their origins and distribution within the population. RT-PCR of both the gag and env genes were sequenced from Yunnan province inhabitants newly diagnosed with HIV-1. Sequence data from 290 samples were used for statistical analysis of subtype distribution and phylogenetic tree construction. Distribution data were adjusted to account for different geographical distributions of HIV-1 subtypes in the population. Phylogenetic an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 14 publications
(25 reference statements)
1
10
0
Order By: Relevance
“…53 Recent data on HIV subtypes circulating in Myanmar are limited to the ChinaMyanmar border, mostly in PWID populations. [54][55][56] A breakdown of HIV-1 in Yunnan includes CRF07_BC (18.9%), CRF08_BC (39.1%), and CRF01_AE (22.4%) 57 ; pol sequences in newly diagnosed HIV-infected individuals from Dehong county, Yunnan, showed that subtype C accounted for 43.1%, URF for 18.4%, CRF01_AE for 17.7%, B for 10.7%, CRF08_BC for 8.4%, and CRF07_BC for 1.7% 58 ; near-full-genome sequencing results show that many new CRFs have been generated in this region. [59][60][61][62] In India, subtype C is the predominant circulating subtype, [63][64][65][66] irrespective of the route of transmission, 67,68 and has been reported as one of the parental strains of CRF07_BC and CRF08_BC in China.…”
Section: Hiv-1 Molecular Epidemiologymentioning
confidence: 99%
“…53 Recent data on HIV subtypes circulating in Myanmar are limited to the ChinaMyanmar border, mostly in PWID populations. [54][55][56] A breakdown of HIV-1 in Yunnan includes CRF07_BC (18.9%), CRF08_BC (39.1%), and CRF01_AE (22.4%) 57 ; pol sequences in newly diagnosed HIV-infected individuals from Dehong county, Yunnan, showed that subtype C accounted for 43.1%, URF for 18.4%, CRF01_AE for 17.7%, B for 10.7%, CRF08_BC for 8.4%, and CRF07_BC for 1.7% 58 ; near-full-genome sequencing results show that many new CRFs have been generated in this region. [59][60][61][62] In India, subtype C is the predominant circulating subtype, [63][64][65][66] irrespective of the route of transmission, 67,68 and has been reported as one of the parental strains of CRF07_BC and CRF08_BC in China.…”
Section: Hiv-1 Molecular Epidemiologymentioning
confidence: 99%
“…One hypothesis for the high false negative rate is that perhaps the third generation ELISA assays, whether domestic or imported, did not thoroughly address the circulating clades of HIV strains among blood donors in China that reportedly displayed unique distribution of major circulating recombinant forms BC (CRF_BC) and CRF_AE (Zeng et al , ). Four of the nine false negative donors were identified in Kunming, Yunnan Province, which is considered the epicentre of the HIV epidemic in China and the source of most circulating and evolving HIV subtypes (Chen et al , ; Su et al , ). These donors, together with those from other blood centres, might have unique circulating clades that would be missed by one round ELISA screening.…”
Section: Discussionmentioning
confidence: 99%
“…HIV-1 subtypes has been documented to circulate in Yunnan, including CRF01_AE, B, C, CRF07_BC, CRF08_BC, and various URFs. 15 Some of these HIV-1 subtypes were introduced from neighboring countries such as Myanmar. 16,17 Moreover, China-Myanmar border area is considered as the geographical hotspot with extensive HIV recombination.…”
Section: A Multiplementioning
confidence: 99%
“…As the neighboring area of Myanmar, Yunnan province not only been considered as the first HIV‐1 epidemic and the most HIV‐1 affected region, but also is thought to be the epicenter of HIV‐1 in China . A multiple HIV‐1 subtypes has been documented to circulate in Yunnan, including CRF01_AE, B, C, CRF07_BC, CRF08_BC, and various URFs . Some of these HIV‐1 subtypes were introduced from neighboring countries such as Myanmar .…”
Section: Introductionmentioning
confidence: 99%